Analisis SWOT terhadap Penerapan Marketing Mix 7P dalam Peningkatan Penjualan PT. Hanin Wisata Semesta - Syarifah, Tsaniyatas; Saqofa Nabilah Aini; Zamrodul Ardina (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2024)
This research aims to analyze the 7P marketing mix strategy at PT. Hanin Wisata Semesta using SWOT analysis. SWOT analysis is used to find the strengths, weaknesses, opportunities, and threats of the Hanin Travel company. SWOT analysis is carried out on each 7P marketing mix variable in the company. The results of this research are that the 7P marketing mix strategy has an impact on increasing or decreasing sales at PT. Hanin Wisata Semesta. From the results of the SWOT analysis, PT. Hanin Wisata Semesta must make improvements according to the location of the error so that the sales value increases further.